The Influence Of Promotion Through Instagram Social Media On The Decision To Visit The Rumah Ulin Arya Tourism Object (Study Of Instagram Followers @Rumahulinarya) - Asshari, Ahmad; Purwanti, Silviana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Rumah Ulin Arya is one of the family tourist destinations in Samarinda city that offers a variety of activities, attractions, and complete facilities. To enhance and maintain public interest in visiting the destination as a place of cultural and historical education, as well as entertainment, a strategy is needed, particularly in publicizing all activities related to the tourist destination through promotion on Instagram social media.This study aims to determine the influence of promotion through Instagram social media on the decision to visit Rumah Ulin Arya. This research uses a quantitative method with a survey approach. Data collection methods in this study involve distributing questionnaires via Google Forms to 100 people who follow the Instagram account @rumahulin.arya. The concepts used in this study are social media promotion and the decision to visit. The results of this study indicate that there is an influence of promotion through Instagram social media on the decision to visit by 44.1%, with the remaining 55.9% influenced by other factors not examined in this study. The strength of the relationship between the variables tends to be positive, with a figure of 0.664.